ANALISIS PENERIMAAN KARYAWAN POSISI FIELD COLLECTOR MENGGUNAKAN ALGORITMA C4.5 PADA PT. PRISMAS JAMINTARA JAKARTA - Ayuni Asistyasari; Taufik Baidawi (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
PT Prismas Jamintara one the service human resources company every month selected employee on Field Collector position for customer needed. The process of human resources needs to have criteria such as Old, Education, Experience, and vehicle. The purpose of a processed employee is customer need. Algorithm C4.5 is one of the methods for analyzing data used entropy and gain concept. With that Algorithm. made the decision tree to measure the best criteria and get accuracy value 71,54%+/-%+/-9,13%, precision 80,47% +/-8,16 and recall 83,78% +/-9,29% with ROC value 0,721.